Exploring the Role of C-H-II Interactions on the Structural Stability of Membrane Proteins - K. RAMANATHAN; V. SHANTHI; RAO SETHUMADHAVAN (International Journal of Pharma and Bio Sciences, 2010)
C–H...π interactions are known to be important contributors to protein stability. In this study, we have analyzed the influence of C–H…π interactions on the structural stability of membrane proteins. In the data set, a total of 408 C–H….π interactions were observed. The most prominent representatives are the interactions between aromatic C–H donor groups and aromatic π acceptors. Ninety four percent of the C–H….π interactions between side chain to side chain and remaining six percent of the C–H….π interactions were observed between side-chain to side-chain five-membered aromatic ring. Long-range C–H….π interactions are the predominant type of interactions in membrane proteins data set. The secondary structure preference, solvent accessibility and stabilization centers of C–H….π interacting residues were estimated. Moreover, the study shows that 72% of the donor residues and 68% of the acceptor residues are highly conserved. . It is concluded that the C–H….π interaction can, indeed, be categorized as a true stabilizing force in membrane proteins.